The Shahi ʿIdgah of 1312 at Rapri (Uttar Pradesh): A Landmark in Indian Glazed Tiles - Porter, Yves (Muqarnas, 2018)
The Shahi ʿIdgah at Rapri (Uttar Pradesh), which dates to 1312, was built by Malik Kafur, the general of the Delhi sultan ʿAlaʾuddin Khalji (1296-1316). The village of Rapri was part of Malik Kafur's fief and an important station for the army, as it commanded a ford on the Yamuna River. ʿIdgāhs, sometimes translated as "wall-mosques," are extra-urban, open prayer spaces for accommodating large congregations during the two main religious festivals (ʿīds). The Rapri ʿīdgāh constitutes a major landmark in the architecture of the Delhi Sultanate, mainly because of its exceptional decoration of turquoise-glazed tiles, the oldest example of its kind still in situ. Although often considered a technique that originated in the Iranian domains, the making of glazed tiles was already known in the Kushan period (first to fourth century CE), and some findings have been excavated from Buddhist contexts in the nearby Mathura region. This study shows the link between the tiles of Rapri and later fourteenth century examples, and with glazed pottery.